Analysis of Critical Thinking Ability in Artificial Intelligence-Assisted Guided Inquiry Model Based on Mathematical Disposition - Putri, Sanianajiba Nugroho; Junaedi, Iwan; Kharisudin, Iqbal (Universitas Negeri Semarang, 2025)
This research aims to analyze the quality of implementing the Guided Inquiry learning model assisted by Artificial Intelligence on students’ critical thinking abilities and to describe students' critical thinking abilities based on their mathematical disposition after being given the Guided Inquiry learning model assisted by Artificial Intelligence. This study employed a mixed-methods approach used a sequential explanatory design. The quantitative research involved a population of 10th-grade students at MA Annidlomiyah. The selected samples were class X B as the experimental group and class X A as the control group. Research instrument in the form of a test of mathematical critical thinking abilities, mathematical disposition questionnaires, an interview, and student worksheets with data analysis was used with IBM SPSS 16. The qualitative research described critical thinking abilities based on high, medium, and low mathematical dispositions. The research results show that 1) The quality of implementing the Guided Inquiry model assisted by Artificial Intelligence met valid criteria at the planning stage, achieved a very good category at the implementation stage, and fulfilled learning effectiveness at the evaluation stage of results. 2) The description of students' critical thinking abilities is as follows: (a) Students with a high mathematical disposition demonstrated very good critical thinking abilities and were able to meet all four indicators of critical thinking ability. (b) Students with a medium mathematical disposition had critical thinking abilities that were not as good as those with a high mathematical disposition. Most students only met two to three indicators of critical thinking ability. (c) For students with a low mathematical disposition, there were two differences in critical thinking ability observed in this study. Some met three indicators, while others only met one indicator.